Model Supervisi Digital Adaptif dalam Pengembangan Kompetensi Orang Dewasa di Era Society 5.0 (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The Society 5.0 era brings fundamental changes in the way humans work, learn, and develop. Amid these changes, adult competency development requires a more responsive and adaptive supervision approach to individual needs and technological demands. This study aims to analyze the need for digital supervision in adult competency development and formulate an adaptive digital supervision model relevant to the demands of Society 5.0. The method used is qualitative research with a literature study approach through content analysis, thematic analysis, and conceptual synthesis of literature from various selected scientific sources. The results show that adults in this era face real challenges in terms of digital literacy, critical thinking skills, and adaptation to rapid technological changes. In response to these challenges, the proposed adaptive digital supervision model consists of five main stages: needs analysis, digital planning, supervision implementation, monitoring and evaluation, and adaptive feedback. This model is characterized by being human-centered, adaptive, data-driven, collaborative, and oriented towards continuous improvement. The implications of this model include improving professional competency, strengthening digital literacy, and supporting lifelong learning, which aligns with the vision of Society 5.0.